Correlation Between Materials-induced Irritation and Oral Mucosal Lesions - Anwar, Rabia; Bibi, Ayesha (Biological and Clinical Sciences Research Journal, 2025)
Material-induced irritation of the oral mucosa can result in a spectrum of lesions, ranging from benign reactive changes to potentially malignant disorders and oral squamous cell carcinoma (OSCC). Establishing correlations between specific irritants and lesion types is critical for prevention, early diagnosis, and effective management. Objective: To evaluate the relationship between material-induced irritation and the development of oral mucosal lesions, with emphasis on risk factors, clinical presentation, and histopathological patterns. Methods: This cross-sectional study was conducted in the Department of Dental Materials, Ayub Medical College, Abbottabad, from April to September 2024. A total of 160 patients aged ≥18 years with clinically and histopathologically confirmed oral mucosal lesions related to irritant exposure (mechanical, chemical, or metallic) were included. Detailed histories, clinical examinations, and photographic documentation were undertaken, followed by incisional or excisional biopsies for diagnosis. Lesions were classified as reactive, potentially malignant disorders (PMDs), or OSCC. Data were analyzed using chi-square and Pearson correlation tests, with p<0.05 considered significant. Results: Of the participants (mean age 43.5 ± 12.2 years; 57.5% male), 71.3% had lesions linked to chronic mechanical irritants, while 28.7% were associated with chemical irritants. Buccal mucosa (42.5%) and lateral tongue (28.1%) were the most common sites. Histopathology revealed reactive lesions in 47.5%, PMDs in 32.5%, and OSCC in 20.0% of cases. Mechanical irritants (ill-fitting dentures, orthodontic appliances) were predominantly associated with reactive lesions, whereas chemical irritants (smokeless tobacco, nicotine) correlated more with PMDs and OSCC. Metallic restorations were significantly linked with lichenoid lesions. A strong positive correlation was found between duration of irritant exposure and lesion severity (r=0.62, p=0.002). Conclusion: Chronic material-induced irritation is a significant risk factor for oral mucosal pathology, with prolonged exposure markedly increasing the likelihood of malignant transformation. Early detection and removal of irritants, patient education, and preventive measures are vital to reduce lesion progression and improve oral health outcomes.